The Moderating Role of Quality Improvement in Improving Brand Credibility - Akmal Mundiri; Inayatul Firdausiah (At-Tarbiyat, 2022)
This research aims to find out what are the new roles that Pondok Pesantren Nurul Jadid does in increasing consumer confidence in the services provided by Pondok Pesantren Nurul Jadid. This research uses a qualitative approach with this type of case study research. Data collection techniques are carried out through interviews supported by observations of some of the activities in the study subjects. The results of this study found that the role of quality improvement carried out by Pondok Pesantren Nurul Jadid began with monitoring changes through change management, identification of improvement formulations, fulfillment of completeness of infrastructure improvement facilities, optimization of cooperation performance between teams, in-service training, environmental analysis in evaluation, identification of goals and targets, gap analysis, input, and output identification, monitoring improvements. So it can be concluded that the new role in increasing consumer confidence in Pondok Pesantren Nurul Jadid shows success in attracting its consumers to continue using the services provided by Pondok Pesantren Nurul Jadid.